2015
DOI: 10.5539/ibr.v8n9p57
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Positive Organizational Behavior with Job Satisfaction, Organizational Citizenship Behavior, and Employee Engagement

Abstract: The concept of positive organizational behavior (POB) was introduced several years ago as a way to create competitive advantage. Therefore, organizations pay more attention to Positive Organizational Behavior due to the changing and competitive nature of organizations. And it becomes a major focus area for theory building, research, and application in psychology and now organizational behavior. This paper introduces the emergent concept of POB and its role in organizational work-related performance, and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
3
18
0
5
Order By: Relevance
“…Based on the results of the analysis using structural equation modeling concluded that one of the types of psychological capital is a capability of Managing Talented Worker in The Era of New Psychological Contract employees in building collaboration and give added value a positive effect against the behavior of citizenship employees. this study in line with the research Pouramini and Fayyazi (2015) on the employees in the public organizations in Iran concluded that the ability of the employees to add value influence on organizational citizenship behavior. Fredrickson (2003) conclude that the involvement of the employees in the progressive oriented activities will encourage employees to share creative ideas and provide innovative suggestions for the improvement of the quality of the work.…”
Section: The Influence Of Career Resilience On Organizational Citizensupporting
confidence: 87%
“…Based on the results of the analysis using structural equation modeling concluded that one of the types of psychological capital is a capability of Managing Talented Worker in The Era of New Psychological Contract employees in building collaboration and give added value a positive effect against the behavior of citizenship employees. this study in line with the research Pouramini and Fayyazi (2015) on the employees in the public organizations in Iran concluded that the ability of the employees to add value influence on organizational citizenship behavior. Fredrickson (2003) conclude that the involvement of the employees in the progressive oriented activities will encourage employees to share creative ideas and provide innovative suggestions for the improvement of the quality of the work.…”
Section: The Influence Of Career Resilience On Organizational Citizensupporting
confidence: 87%
“…hope, resilience and optimism) (Chen, Zeng, Chang, & Cheung, 2019). In a study conducted in Iran, PsyCap was found to be significantly positively correlated with OCB (Pouramini & Fayyazi, 2015). This is supported by other studies (Beal III, Stavros, & Cole, 2013;Sepeng, 2016) using South African samples where PsyCap was found to be statistically significantly correlated with OCB; thus, employees with high PsyCap engaged more in OCB than those with low PsyCap.…”
Section: Empirical Literature Review the Relationship Between Psychological Capital And Organisational Citizenship Behaviourmentioning
confidence: 51%
“…Cottini found involving workers in setting work practices led to less attrition, avoiding rehiring costs while allowing workers to gain experience (Cottini et al, 2011). (Hsu and Chen, 2015), organisational citizenship behaviour (Qadeer and Jaffery, 2014;Pouramini and Fayyazi, 2015;Nolzen, 2018), and a "mastery-oriented mindset toward training" (Luthans et al, 2011). Even in challenging workplaces, PsyCap and well-being can allow workers to feel less stressed and more resourceful and engaged, enhancing productivity (Siu et al, 2014;Mazzetti et al, 2016;Joo and Lee, 2017).…”
Section: Theories Of Well-beingmentioning
confidence: 99%